Frog Skin-Derived Peptides Against Corynebacterium jeikeium: Correlation between Antibacterial and Cytotoxic Activities - Casciaro, Bruno; Loffredo, Maria Rosa; Cappiello, Floriana; Verrusio, Walter; Corleto, Vito Domenico; Mangoni, Maria Luisa (Antibiotics (Basel), 2020)
Corynebacterium jeikeium is a commensal bacterium that colonizes human skin, and it is part of the normal bacterial flora. In non-risk subjects, it can be the cause of bad body smell due to the generation of volatile odorous metabolites, especially in the wet parts of the body that this bacterium often colonizes (i.e., groin and axillary regions). Importantly, in the last few decades, there have been increasing cases of serious infections provoked by this bacterium, especially in immunocompromised or hospitalized patients who have undergone installation of prostheses or catheters. The ease in developing resistance to commonly-used antibiotics (i.e., glycopeptides) has made the search for new antimicrobial compounds of clinical importance. Here, for the first time, we characterize the antimicrobial activity of some selected frog skin-derived antimicrobial peptides (AMPs) against C. jeikeium by determining their minimum inhibitory and bactericidal concentrations (MIC and MBC) by a microdilution method. The results highlight esculentin-1b(1-18) [Esc(1-18)] and esculentin-1a(1-21) [Esc(1-21)] as the most active AMPs with MIC and MBC of 4–8 and 0.125–0.25 µM, respectively, along with a non-toxic profile after a short- and long-term (40 min and 24 h) treatment of mammalian cells. Overall, these findings indicate the high potentiality of Esc(1-18) and Esc(1-21) as (i) alternative antimicrobials against C. jeikeium infections and/or as (ii) additives in cosmetic products (creams, deodorants) to reduce the production of bad body odor.